The COVID-19 pandemic and budget shortfalls in the local governments in Slovakia - Andrea Cajkova; Ivana Butoracová Šindleryová; Michal Garaj (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
The study focuses on budget policy implementation at the level of local governments in Slovakia in connection with the COVID-19 pandemic. The research problem focuses on identifying shortfalls in initially planned funds to local government budgets caused by the COVID-19 crisis and the potential ways individual local governments in Slovakia have been able to cover them. The aim of the study is to identify the accepted crisis mechanisms for solving financial shortfalls in local budgets due to the pandemic situation. In the descriptive-analytical study qualitative and quantitative methods were used. Available information on Slovakia indicates several main findings. It has been confirmed the pandemic had negative effects for of all local governments nationwide, regardless of the status of the town or municipality. The municipal fiscal imbalance as a result of the Covid-19 crisis and municipal financial resources are not commensurate and the most important tool that municipalities have the opportunity to use is their reserve funds. Consequently, they have become highly dependent on repayable financial assistance from the state. The authors contribute to the ongoing debate about the current Covid-19 crisis and its consequences for local government finance.
Keywords: D73; H12; H72; H83; 330; Local Budgets; Budget Shortfalls; Covid-19; Local Governments; Slovakia